Semantic web services for manufacturing workflow - Madhav Raj Maharjan (2009)
Globalization, improvement in processes and technology, demand for customized goods nhave introduced new, unique challenges especially to the manufacturing industry forcing them to be more agile, adaptable, and flexible than ever before. As agile business practices have become core requirements, enterprises have to adapt & develop innovative, improved and integrated responses to market changes. Service-oriented web services and semantic web technology have appeared as promising approaches to address these challenges by seamlessly integrating heterogeneous systems, adding semantics to information flow, promoting reuse of knowledge base, interoperability, automation and reuse of enterprise wide resources & processes. Semantic web service aims to reduce the collaboration cost, increase agility and flexibility, hence, increase productivity by automating enterprise processes. This project explores and illustrates the potential application of semantic web technology in context of a manufacturing enterprise. It demonstrates the use of Web Ontology Languages (OWL & OWL-S) to formally describe terms, key concepts and their relationships, as well as manufacturing processes to build knowledge base of the manufacturing domain. We propose context independent top level ontology for manufacturing domain that can be extended fore specific applications, illustrate advantages of semantic web technology and present use cases of semantic web technology for the manufacturing enterprise.